Causative role of a novel intronic indel variant in FBN1 and maternal germinal mosaicism in Marfan syndrome - Ying Bai; Yue Sun; Chenguang Yu; Yanjie Xia; Jing Wu; Li Wang; Yong Gao; Xin Tu; Xiangdong Kong (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Marfan syndrome (MFS) is an autosomal dominant connective tissue disease with wide clinical heterogeneity, and mainly caused by pathogenic variants in fibrillin-1 (FBN1). Methods A Chinese 4-generation MFS pedigree with 16 family members was recruited and exome sequencing (ES) was performed in the proband. Transcript analysis (patient RNA and minigene assays) and in silico structural analysis were used to determine the pathogenicity of the variant. In addition, germline mosaicism in family member (Ι:1) was assessed using quantitative fluorescent polymerase chain reaction (QF-PCR) and short tandem repeat PCR (STR) analyses. Results Two cis-compound benign intronic variants of FBN1 (c.3464–4 A > G and c.3464-5G > A) were identified in the proband by ES. As a compound variant, c.3464-5_3464-4delGAinsAG was found to be pathogenic and co-segregated with MFS. RNA studies indicated that aberrant transcripts were found only in patients and mutant-type clones. The variant c.3464-5_3464-4delGAinsAG caused erroneous integration of a 3 bp sequence into intron 28 and resulted in the insertion of one amino acid in the protein sequence (p.Ile1154_Asp1155insAla). Structural analyses suggested that p.Ile1154_Asp1155insAla affected the protein’s secondary structure by interfering with one disulfide bond between Cys1140 and Cys1153 and causing the extension of an anti-parallel β sheet in the calcium-binding epidermal growth factor-like (cbEGF)13 domain. In addition, the asymptomatic family member Ι:1 was deduced to be a gonadal mosaic as assessed by inconsistent results of sequencing and STR analysis. Conclusions To our knowledge, FBN1 c.3464-5_3464-4delGAinsAG is the first identified pathogenic intronic indel variant affecting non-canonical splice sites in this gene. Our study reinforces the importance of assessing the pathogenic role of intronic variants at the mRNA level, with structural analysis, and the occurrence of mosaicism.